Episodic memory loss is related to hippocampal-mediated β-amyloid deposition in elderly subjects - Mormino, E. C.; Kluth, J. T.; Madison, C. M.; Rabinovici, G. D.; Baker, S. L.; Miller, B. L.; Koeppe, R. A.; Mathis, C. A.; Weiner, M. W.; Jagust, W. J. (Brain (London, England : 1878), 2009)
Although β-amyloid (Aβ) plaques are a primary diagnostic criterion for Alzheimer's disease, this pathology is commonly observed in the brains of non-demented older individuals. To explore the importance of this pathology in the absence of dementia, we compared levels of amyloid deposition (via ‘Pittsburgh Compound-B’ (PIB) positron emission tomography (PET) imaging) to hippocampus volume (HV) and episodic memory (EM) in three groups: (i) normal controls (NC) from the Berkeley Aging Cohort (BAC NC, n = 20); (ii) normal controls (NC) from the Alzheimer's disease neuroimaging initiative (ADNI NC, n = 17); and (iii) PIB+ mild cognitive impairment subjects from the ADNI (ADNI PIB+ MCI, n = 39). Age, gender and education were controlled for in each statistical model, and HV was adjusted for intracranial volume (aHV). In BAC NC, elevated PIB uptake was significantly associated with smaller aHV (P = 0.0016) and worse EM (P = 0.0086). Within ADNI NC, elevated PIB uptake was significantly associated with smaller aHV (P = 0.047) but not EM (P = 0.60); within ADNI PIB+ MCI, elevated PIB uptake was significantly associated with both smaller aHV (P = 0.00070) and worse EM (P = 0.046). To further understand these relationships, a recursive regression procedure was conducted within all ADNI NC and PIB+ MCI subjects (n = 56) to test the hypothesis that HV mediates the relationship between Aβ and EM. Significant correlations were found between PIB index and EM (P = 0.0044), PIB index and aHV (P < 0.0001), as well as between aHV and EM (P < 0.0001). When both aHV and PIB were included in the same model to predict EM, aHV remained significant (P = 0.0015) whereas PIB index was no longer significantly associated with EM (P = 0.50). These results are consistent with a model in which Aβ deposition, hippocampal atrophy, and EM occur sequentially in elderly subjects, with Aβ deposition as the primary event in this cascade. This pattern suggests that declining EM in older individuals may be caused by Aβ-induced hippocampus atrophy.